THE EFFECT OF USING REAL OBJECTS IN DEVELOPING STUDENTS’ SPEAKING ABILITY: AN EXPERIMENTAL STUDY AT THE FIRST YEAR STUDENTS OF D4 TEKNOLOGI REKAYASA PERANGKAT LUNAK POLITEKNIK MEDICA FARMA HUSADA MATARAM IN ACADEMIC YEAR 2024/2025 - Permana, Yan Reiza (Yayasan Nusantara Hasana Berdikari, 2025)
This research aims to find out the effect of using real objects to develop students’ speaking skill. This research uses experimental method. The research is conducted at the second year students of D4 Teknologi Rekayasa Perangkat Lunak Politeknik Medica Farma Husada Mataram in Academic Year 2024/2025. The research takes randomly for the samples consist of four classes with 64 students to identify the data the research uses experimental and control class. The sample each class consist of 32 students. The techniques of data collection uses pre-test and post-test. The data is obtained from t-test formula. The result of research shows that value of t- test is 4.8 it is higher than t-table with significant level is.05(1.999) and .01( 2.6575)and df is 62. The mean score of the experimental group is 32.7 and the mean score of the control group is 15.4 it means that the score of the experimental group is higher than the control grouped. The alternative hypothesis is accepted and null hypothesis is rejected. Thus real objects can develop students’’ speaking skill.